Review the Aspects of Legal Protection for Consumers in E-Commerce Transactions in Indonesia - Noor Bagja, Hafied; Surayya Mohd Saudi, Nur (International Journal of Psychosocial Rehabilitation, 2020)
The development of virtual business systems, such as virtual stores and virtual companies, where businesspeople run their business and commerce through the internet and no longer rely on conventional real company business. Various problems that arise as a result of information technology and must be faced by the law should have been quite clear and predictable. So what is the legal challenge of e-commerce development, and what is the role of the government in encouraging the emergence of startups (startups) in the e-commerce field? The research method used uses a qualitative and descriptive approach, with data analysis techniques using an interactive model. The results of the study stated that the challenges of novice business players must be able to see the potential and opportunities of business opportunities as a result of the development of information technology by utilizing e-commerce. It is important to understand and understand by them various issues related to legal challenges in building electronic commerce businesses, such as business contracts, as an effort to minimize legal issues that can occur in the future, and the government prepares various e-commerce regulations, namely the Ministry of Communication and Information, the Ministry of Trade, the Ministry of Finance, and the Financial Services Authority, as material for policy making and the formation of e-commerce regulations.